British and American policy with regard to Greece 1943-1947: the transition from British to American patronage - Frazier, Robert (1989)
British Foreign Office efforts during World War II to ensure the peaceful restoration of the King and his Government-in-Exile after Greece was liberated were frustrated by the King's refusal, with Churchill's support, to submit himself to a plebiscite. The United States refused to become involved (except for an unwarranted interference by Roosevelt) and generally disapproved of British policies. The return of the Government-in-Exile to Greece without a firm commitment by the King concerning his future resulted in a Communist-led revolt which was ended only by British military intervention and by Churchill finally forcing the King to accept a regency and the plebisicite.